Comparative histological and immunohistochemical study on the effect of platelet rich plasma/minoxidil, alone or in combination, on hair growth in a rat model of androgenic alopecia. (April 2022) - Elsebay, Sara Abdel Gawad; Nada, Hoda Fouad; Sultan, Nancy Sultan Saad; El-Waseef, Dalia Alaa El-Din Aly
Highlights: Platelet Rich Plasma is effective and safe in treatment of experimentally induced androgenic alopecia in rats. PRP is more effective than minoxidil in treatment of AGA. The best results were obtained when PRP and minoxidil were administered together The highest number of Ki 67 positive cells was seen in rats receiving both minoxidil and PRP. Abstract: Background: Androgenic alopecia (AGA) is the commonest cause of hair loss in men with limited treatment options. Aim of the work: To compare the efficacy of PRP and minoxidil on experimentally induced AGA in adult male albino rats. Materials and methods: Thirty male albino rats were used. Group I (control group). Group II (AGA group): received testosterone only. Group III: received topical minoxidil. Group IV: received PRP /three days. Group V: received PRP and topical minoxidil. Results: Groups III, IV, and V showed significant increase in mean epidermal thickness, mean numbers of total hair follicles and anagen hair follicles, and decrease in telogen hair follicles compared to AGA group. Group V showed the best results. AGA group showed perifollicular fibrosis and follicular streamers. They were absent in PRP group and group V. Significant decrease of Ki-67 positive cells in AGA. PRP and minoxidil groups showed a significant increase in number of Ki-67 positive cells compared to control and AGA groups. Group V showed the highest number of Ki-67 positive cells. Conclusion: PRP was more effective than minoxidil in treatment of experimentally induced AGA in rats. The best results were obtained when PRP and minoxidil were administered together.